Public Relations Event Analisis Pada Kegiatan Workshop Kerajinan Bambu Saung Angklung Udjo - Aulia, Ellena Fitri; Hidayat, Dasrun; Purwadhi (Program Studi Ilmu Komunikasi, 2023)
In preserving culture, of course, there must be activities that can be done to maintain cultural resilience. As was done by Saung Angklung Udjo (SAU), which made a bamboo craft workshop which was part of the Public Relations event. The workshop activity is an effort to preserve culture carried out by Saung Angklung Udjo (SAU). The purpose of this study was to determine the design of the bamboo craft workshop program, which would regenerate the seeds of prospective angklung artists. This research uses qualitative research with PR ethnographic study. This study aims to determine the PR communication behavior carried out by the organizers of the workshop activities, namely workshop managers and presenters with visitors or workshop participants. The results of this study indicate that there are stages of the workshop activity program, starting from the preparation analysis stage, strategy stage, implementation, community support, to building reputation. This study uses a relevant model, namely the IPPAR model (Insight, Strategic Program, Program Implementation, Action and Reputation). In carrying out its activities and building its reputation, SAU has basic principles or values, namely UDJO stands for Tenacious, Disciplined, Honest, and Optimistic. In addition, by providing the best possible service so that loyalty and reputation are maintained.